The perspective in formation of romantic relationship of individuals who experienced parental separation - 4 0 16; 5
ABSTRACT: This study aim to fully understand the perspective of people who have separated parents in building their own romantic relationship. By exploring their thoughts and feelings, it can make us understand and empathize with the struggles they went through. The researcher interviewed 12 participants around Manila and Quezon City using a semi-structured interview. The questions are specifically for the experiences, feelings and thoughts of the respondents before, during, and after the parental separation. The participants are chosen regardless of age, sex, marital status, socioeconomic status and religion. Furthermore, the researcher uses non-probability sampling technique in the selection of respondents. The results showed that, people around them especially parents, relatives and friends can help them cope with the separation of their parents. They can be their consultant, role model and/or guide throughout their adversity. Most of characteristics they want in a romantic partner are the personality that is present in their current family, characteristics that are absent on their parents/family that may cause the separation and someone who have a future for their relationship. There are caring, religious, future-oriented, committed, trustworthy and loyal. Participants struggles the most in being anxious and skeptical after the parental separation, they always look at the separation of their parents fearing that in may also happen to them and having a difficult time trusting someone.
Thesis: (B.S. Psychology) - Pamantasan ng Lungsod ng Maynila, 2018.
Keywords: 2 -- 0; 6; 20; 20; 2